Clinical Application of the FoundationOne CDx Assay to Therapeutic Decision‐Making for Patients with Advanced Solid Tumors. (6th January 2021) - Takeda, Masayuki; Takahama, Takayuki; Sakai, Kazuko; Shimizu, Shigeki; Watanabe, Satomi; Kawakami, Hisato; Tanaka, Kaoru; Sato, Chihiro; Hayashi, Hidetoshi; Nonagase, Yoshikane; Yonesaka, Kimio; Takegawa, Naoki; et al.
Abstract: Background: Implementation of personalized medicine requires the accessibility of tumor molecular profiling in order to allow prioritization of appropriate targeted therapies for individual patients. Our aim was to study the role of comprehensive genomic profiling assays that may inform treatment recommendations for patients with solid tumors. Materials and Methods: We performed a prospective study to evaluate the feasibility of application of the FoundationOne CDx panel—which detects substitutions, insertions and deletions, and copy number alterations in 324 genes, select gene rearrangements, and genomic signatures including microsatellite instability and tumor mutation burden (TMB)—to patients with advanced or recurrent solid tumors before its approval in Japan. Results: A total of 181 samples were processed for genomic testing between September 2018 and June 2019, with data being successfully obtained for 175 of these samples, yielding a success rate of 96.7%. The median turnaround time was 41 days (range, 21–126 days). The most common known or likely pathogenic variants were TP53 mutations ( n  = 113), PIK3CA mutations ( n  = 33), APC mutations ( n  = 32), and KRAS mutations ( n  = 29). Among the 153 patients assessed for TMB, the median TMB was 4 mutations/Mb, and tumors with a high TMB (≥10 mutations/Mb) were more prevalent for lung cancer (11/32) than for other solid tumor types (9/121, Fisher's exact test p < .01). No clear trend toward increased efficacy for immune checkpoint inhibitor (ICI) monotherapy or ICI combination chemotherapy in patients with a high programmed cell death–ligand 1 tumor proportion score or a high TMB was apparent. Among the 174 patients found to harbor known or likely pathogenic actionable alterations, 24 individuals (14%) received matched targeted therapy. Conclusion: The FoundationOne CDx assay was performed with formalin‐fixed, paraffin‐embedded tumor specimens with a success rate of >95%. Such testing may inform the matching of patients with cancer with investigational or approved targeted drugs. Implications for Practice: This prospective cohort study was initiated to investigate the feasibility and utility of clinical application of FoundationOne CDx. A total of 181 samples were processed for genomic testing between September 2018 and June 2019, with data being successfully obtained for 175 of these samples, yielding a success rate of 96.7%, and 24 individuals (14%) received matched targeted therapy. Abstract : Comprehensive genomic profiling assays can identify multiple actionable genetic alterations that may inform treatment recommendations for patients with solid tumors. This article evaluates the feasibility of the application of the FoundationOne CDx panel to patients with advanced or recurrent solid tumors.